Combatting the imbalance of sex ratio at birth: medium-term impact of India's National Programme of Beti Bachao Beti Padhao in the Haryana State of India. Issue 10 (11th September 2021) - Gupta, Rakesh; Singhal, Girdhari Lal; Goyal, Aarti; Kaur, Gurjinder; Purohit, Neha; Prinja, Shankar
Abstract: The Government of India initiated the Beti Bachao Beti Padhao (B3P) programme in 2015 as a flagship initiative to reduce gender imbalance in sex ratio at birth (SRB) and to ensure social protection of girls. The present study was conducted to evaluate the medium-term impact of B3P implementation in Haryana state, from 2015 to 2019, on SRB. Monthly data on SRB were collected for the entire state of Haryana through a civil registration system. Segmented time series regression analysis was used to estimate the variations in SRB after the B3P programme with the help of Winter's additive interrupted time series model. The SRB in Haryana increased from 876 girls per 1000 boys in 2015 to 923 in 2019. The results of the model demonstrated that before the inception of intervention (pre-slope), there was a significant monthly change in SRB of 0.217 (95% confidence interval: 0.144–0.290). Following the B3P programme, SRB was found to increase by 0.835 per month, which implied that an increase of 0.618 (confidence interval: 0.338, 0.898) every month in SRB can be attributed to the B3P programme. This indicated that SRB for the state of Haryana increased at the rate of 7.42 units per year as a result of the B3P programme. B3P has led to a significant improvement in SRB in Haryana state. The continuity of efforts in the same direction with a sustained focus on behaviour change will further help achieve the goal of gender parity in births and child survival.